NRS2002 assesses nutritional status of leukemia patients undergoing hematopoietic stem cell transplantation - Liu, Peng; Zhang, Zhao-Feng; Cai, Jing-Jing; Wang, Bo-Shi; Yan, Xia (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Objective: To discuss whether nutritional risk screening 2002 (NRS2002) is appropriate for nutritional risk screening for leukemia patients before and after hematopoietic stem cell transplantation (HSCT), and whether there are risk differences in other conditions, such as age, gender and matching degree; to find the methods and indicators of nutritional risk screening for these patients before and after HSCT, in order to give timely intervention to guarantee the successful completion of the entire transplantation process. Methods: Nutritional risk of 99 leukemia patients was screened with NRS2002 before and after HSCT. The χ2 test was applied to compare the risk differences between groups such as age, gender and matching degree, while the differences of other enumeration data, such as recent (1-3 months) weight loss, reduced food intake within one week and BMI, were compared by continuity correction. Results: Of the 99 leukemia patients, 22 cases (22.2%) had nutritional risk before HSCT, while all patients had nutritional risk after HSCT; there is no significant difference in nutritional risk between male and female, and patients of less than 30 years old, not-full matched, recent (1-3 months) weight loss, reduced food intake within a week or BMI